Placental DNA Methylation Abnormalities in Prenatal Conotruncal Heart Defects - Liu, Jingjing; Wu, Yuduo; Sun, Hairui; Liu, Xiaowei; Gu, Xiaoyan; Zhao, Ying; Zhang, Ye; Han, Jiancheng; He, Yihua (Frontiers in Genetics, 2022)
Objective: This study aims to characterize the abnormal changes in placental DNA methylation associated with conotruncal heart defects (CTDs) and the level of methylation as epigenetic biomarkers for CTDs detection. Methods: This was a prospective study involving 28 fetuses diagnosed with CTDs in the second trimester at Beijing Anzhen hospital between September 2020 and June 2021. These cases were classified into four groups based on their subtypes. Twelve normal fetuses were used as controls. Placental tissue was obtained after inducing labor in fetuses. To identify differential methylation sites (DMSs) and regions (DMRs) in cases vs controls, an Infinium Human Methylation 850k bead chip was used. Differential methylation was assessed by comparing the β-values for individual CpG loci. Based on the p-value (<0.05), the most discriminating CpG sites were identified. The area under the receiver-operating-characteristics curve (AUC) was used to determine the predictive accuracy of CpG loci with significant methylation changes for CTDs. The function of genes was assessed through KEGG enrichment analysis, Gene Ontology (GO) analysis and KEGG pathway analysis. Results: In comparison to the control group, the DNA methylation of the placental tissue is significantly different in fetuses with CTDs. We identified the most significantly differentially methylated loci and they demonstrated excellent individual predictive accuracy for CTDs detection with AUC > 0.9 in cases compared with controls. HOXD9, CNN1, NOTCH1, and ECE1 were identified as CTDs-detection candidate genes. Conclusion Our study established the abnormal changes in placental methylation associated with CTDs and potential epigenetic biomarkers for CTDs detection.